THE EFFECT OF LIQUIDITY, CAPITAL STRUCTURE, AND FIXED ASSET TURNOVER TO THE FINANCIAL PERFORMANCE OF THE INFRASTRUCTURE SECTOR COMPANIES LISTED IN THE IDX 2019 – 2024 - feriska kuswardani; Nur Endah Fajar Hidayah (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This study aims to analyze the effect of liquidity, capital structure, and fixed asset turnover on financial performance in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2024. The data source of this study is secondary data. The sample in this study amounted to 240 samples obtained from 40 companies over 6 years with a purposive sampling method. This research method uses Descriptive Statistics, Classical Assumption Test, Multiple Linear Regression Analysis, and Hypothesis Testing. The results of this study indicate that Liquidity (CR) has a negative and significant effect on the financial performance (ROA) of infrastructure companies, Capital Structure (DER) has a positive and significant effect on the financial performance (ROA) of infrastructure companies, and Fixed Asset Turnover (FATO) has a positive and significant effect on the financial performance (ROA) of infrastructure companies. Simultaneously, Liquidity (CR), Capital Structure (DER), and Fixed Asset Turnover (FATO) affect the financial performance (ROA) of infrastructure companies listed on the IDX in 2019-2024.